Unveiling BID: a key biomarker in apoptosis post-intracerebral hemorrhage - Kun Dai; Hong-Rong Zhang; Shuai-Yu Ren; Ming-Pei Zhao; Ming-Pei Zhao; Neng Wang; Neng Wang; Hong-Zhi Gao; Hong-Zhi Gao; De-Zhi Kang; De-Zhi Kang; De-Zhi Kang; et al. (Frontiers in Neurology)
BackgroundApoptosis plays a significant role in secondary brain injury following intracerebral hemorrhage (ICH). Currently, the mechanisms related to cell apoptosis after cerebral hemorrhage are still under investigation.MethodsWe identified differentially expressed genes (DEGs) between human ICH patients and normal individuals from the GEO database and conducted GO and KEGG functional enrichment analyses on these DEGs. We then constructed a PPI network and used the MECDE algorithm to identify key genes potentially involved in apoptosis after ICH. Additionally, we identified miRNAs that might regulate apoptotic genes in an mRNA-miRNA interaction network. Finally, we validated the bioinformatics results in a rat ICH model.ResultsIn the human ICH model, 645 DEGs were identified. GO and KEGG analyses indicated that these DEGs are primarily involved in immune response, inflammatory response, and apoptosis. GSEA analysis showed significant enrichment of DEGs in the apoptotic process. By comparing with apoptosis-related genes in the MSigDB database, we identified 110 apoptosis-related genes among the 645 DEGs. Further PPI and MOCDE analyses of these apoptosis-related genes revealed that BID might be a key gene involved in apoptosis after ICH, which was validated within the rat model of ICH. The mRNA-miRNA interactions network construction suggested that miR1225-3p may be an important miRNA involved in regulating BID expression after ICH.ConclusionBID plays a critical role in the regulation of apoptosis following intracerebral hemorrhage and serves as a key biomarker in the apoptotic process after hemorrhage.